Hubungan Tingkat Pengetahuan dengan Gaya Hidup pada Penderita Hipertensi di Kelurahan Legok Kota Jambi - Maimaznah, Maimaznah; Hidayat, Muhammad (3031-8572, 2024)
Hypertension is persistent blood pressure where the systolic pressure is above 140 mmHg and the diastolic pressure is above 90 mmHg. In the elderly, hypertension is defined as a systolic pressure of 160 mmHg and a diastolic pressure of 90 mmHg. The causes of hypertension include emotional disturbances, obesity, excessive alcohol consumption, excessive stimulation of coffee and tobacco, drugs and heredity. These causes include the influence of lifestyle, while the lifestyle itself is a daily habit, in English